Molluscicidal activity and bioassay-guided fractionation of crude extracts of Annona squamosa L. (Fam. Annonaceae) against oncomelania quadrasi - Obispo, Krishelle Anne M.
The seed, leaf, and bark of Annona squamosa L. (Fam. Annonaceae) were screened for molluscicidal activity, using the molluscicidal bioassay against Oncomelania quadrasi. The crude aqueous extract of the bark among the six extracts, exhibited molluscicidal activity at the concentration of 0.1 g/L. The % mortality of the O. quadrasi showed an increasing trend as the concentration of the crude aqueous bark extract is increased. The crude aqueous bark extract was subjected to bioassay-guided fractionation using modified Kupchan Partitioning resulting to aqueous, hexane, ethyl acetate, and methanol fractions. Of the four solvent fractions, the aqueous fraction showed the highest molluscicidal activity with % mortality reaching up to 50%. Tannins, flavonoids and terpenoids were found in the aqueous fraction of the crude aqueous bark extract, which may be the responsible compound that contributed to its molluscicidal activity. The results suggest that A. squamosa may be used as a potential molluscicidal agent against O.quadrasi for the eradication of schistosomiasis.